Genetic diversity of rhinoviruses detected at a tertiary hospital in Catalonia (Spain) during the 2014–2017 seasons. (November 2018) - Andrés, Cristina; Peremiquel-Trillas, Paula; Gimferrer, Laura; Isern, Anna; Piñana, Maria; Rodrigo-Pendás, José Ángel; Codina, Maria Gema; Martín, María del Carmen; Fuentes, Francisco; Rubio, Susana; Campins-Martí, Magda; Pumarola, Tomàs; et al.
Aim: To describe the genetic diversity of rhinovirus (RV) from patients attended at a tertiary hospital in Barcelona (Spain) from October 2014 to May 2017.Methods: RV detection was performed by real-time multiplex RT-PCR. A specific real-time quantitive retrotranscription PCR (qRT-PCR) was carried out to select those samples (Ct < 35) for molecular characterization based on partial VP4/2 protein.Results: Phylogenetic characterization revealed proportions of 63% RV-A, 6% RV-B and 31% RV-C (119 different types). RV-A circulated throughout all the study period, with a minor circulation during winter, just when RV-C prevailed. Differences between age medians by RV-specie were reported.Conclusion: The large genetic diversity of RV detected in our area is described here. The variable cocirculation of multiple RV types is also reported, showing differences by age.